1999
DOI: 10.1097/00001756-199901180-00025
|View full text |Cite
|
Sign up to set email alerts
|

When a rubber hand ‘feels’ what the real hand cannot

Abstract: We examined a patient who was clinically much better at reporting tactile stimulation when he could see his stimulated hand. Experimentally, we found that he had difficulty detecting taps accompanied by a salient (but not predictive) light located directly above his concealed hand. However, his performance was dramatically improved if the light was attached to a rubber hand situated in line with the patient's hidden hand. Previous studies have suggested that tactile sensitivity can be improved by nearby visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 8 publications
6
29
0
Order By: Relevance
“…Specifically, they might use tactile information about the midpoint of the line to correct the shift produced by the visual arrowheads. Evidence from brain-damaged patients (Rorden, Heutink, Greenfield, & Robertson, 1999) and neurologically unimpaired participants (Serino, Padiglioni, Haggard, & Ladavas, 2009;Taylor-Clarke, Kennett, & Haggard, 2002), indicates that vision may improve tactile detection, supporting an interpretation of this sort for the present observation that in the bimodal visuohaptic condition the illusory "error" is reduced in size.…”
Section: Discussionsupporting
confidence: 80%
“…Specifically, they might use tactile information about the midpoint of the line to correct the shift produced by the visual arrowheads. Evidence from brain-damaged patients (Rorden, Heutink, Greenfield, & Robertson, 1999) and neurologically unimpaired participants (Serino, Padiglioni, Haggard, & Ladavas, 2009;Taylor-Clarke, Kennett, & Haggard, 2002), indicates that vision may improve tactile detection, supporting an interpretation of this sort for the present observation that in the bimodal visuohaptic condition the illusory "error" is reduced in size.…”
Section: Discussionsupporting
confidence: 80%
“…This observed increase in tactile sensitivity is likely due to participants directing attention towards the site of stimulation. A neutral visual stimulus presented on or near a body part can lead to a shift in attentional focus toward that area [41], and it has been demonstrated that even noninformative vision can decrease tactile thresholds and increase spatial resolution for touch sensation when attention is directed toward the stimulated arm [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Multisensory research indicates that a neutral visual stimulus, such as a light flash, can lead to a tactile attention shift toward a nearby body part [13] and that noninformative vision can decrease a patient's threshold for touch sensation (see Refs. [14,15]). When checking for signs of illness, patients with MUS are commonly reported to use visual inspection (e.g., mirror gazing).…”
Section: Discussionmentioning
confidence: 99%